Concepções e práticas dos atores do processo de gestão democrática nas escolas da rede municipal de ensino de João Pessoa (2016-2023) - Andrade, Wellingta Magnolia Lacerda Leite de (2023)
This thesis presents the results of a study conducted in three schools of the Municipal Education Network of João Pessoa, Paraíba, Brazil. The main objective was to analyze the pedagogical and administrative conceptions and practices of school managers following a change in their appointment system, resulting from a decision by the Paraíba State Court of Justice that eliminated direct elections for the position. In recent decades, school management has faced significant challenges, requiring an approach that addresses legal and social demands, particularly concerning the participation of all involved segments. These issues have been frequently debated and incorporated into educational policy agendas. In this study, we aimed to align the actions in schools with Goal 19 of the National Education Plan (PNE) 2014-2024, which focuses on the democratization of public education. Regarding the research objectives, we adopted an exploratory approach, considering a gap in studies on this topic in this educational network. Concerning the methodology, we employed a qualitative approach, justified by our goal to analyze phenomena occurring in specific contexts, considering time, location, and culture. We selected 3 (three) schools from a universe of 101 (one hundred and one), representing different sizes and geographical locations in João Pessoa. The field research involved systematic observation and conducting semi-structured interviews. Research participants included two managers (one pedagogical and one administrative), one specialist, two teachers, two staff members, and two mothers, all members of the School Deliberative Council of each school. In total, 27 (twenty-seven) subjects were interviewed. In the analysis of results, we used graphs to better understand the different realities and perspectives of the interviewees. Additionally, we contextualized and established relationships between legal guidelines and democratic practices in schools from 2016 to 2023 when school managers began to be appointed directly by the executive chief, as determined by the TJPB ruling. It is important to note that our focus was not to test or confirm a hypothesis but to make discoveries and relate the obtained data to literature, foundational documents, and field research. We found that our study fits into a case study, following Yin's perspective (2010), as all stages of the research, from planning to the analysis of interviewees' discourses, emphasize interpretation in a specific context, using a variety of information sources, allowing for some generalizations. We argue that, according to the results in the researched schools, Democratic Management does not necessarily depend on the process of choosing managers by the school community; however, this is one of the elements of participation and democracy of great relevance. Democracy primarily depends on the effective implementation of collegial bodies, daily participative work, and decisions, ensuring everyone contributes to achieving the school's social function and its core objective: improving the quality of education in municipal public schools in João Pessoa.